The Role of Snow in Controlling Halogen Chemistry and Boundary Layer Oxidation During Arctic Spring: A 1D Modeling Case Study. Issue 5 (7th March 2022) - Ahmed, Shaddy; Thomas, Jennie L.; Tuite, Katie; Stutz, Jochen; Flocke, Frank; Orlando, John J.; Hornbrook, Rebecca S.; Apel, Eric C.; Emmons, Louisa K.; Helmig, Detlev; Boylan, Patrick; Huey, L. Gregory; et al.
Abstract: Reactive chlorine and bromine species emitted from snow and aerosols can significantly alter the oxidative capacity of the polar boundary layer. However, halogen production mechanisms from snow remain highly uncertain, making it difficult for most models to include descriptions of halogen snow emissions and to understand the impact on atmospheric chemistry. We investigate the influence of Arctic halogen emissions from snow on boundary layer oxidation processes using a one‐dimensional atmospheric chemistry and transport model (PACT‐1D). To understand the combined impact of snow emissions and boundary layer dynamics on atmospheric chemistry, we model Cl2 and Br2 primary emissions from snow and include heterogeneous recycling of halogens on both snow and aerosols. We focus on a 2‐day case study from the 2009 Ocean‐Atmosphere‐Sea Ice‐Snowpack campaign at Utqiaġvik, Alaska. The model reproduces both the diurnal cycle and high quantity of Cl2 observed, along with the measured concentrations of Br2, BrO, and HOBr. Due to the combined effects of emissions, recycling, vertical mixing, and atmospheric chemistry, reactive chlorine is typically confined to the lowest 15 m of the atmosphere, while bromine can impact chemistry up to and above the surface inversion height. Upon including halogen emissions and recycling, the concentration of HO x (HO x  = OH + HO2 ) at the surface increases by as much as a factor of 30 at mid‐day. The change in HO x due to halogen chemistry, as well as chlorine atoms derived from snow emissions, significantly reduce volatile organic compound lifetimes within a shallow layer near the surface. Key Points: A combination of factors including snow emissions, vertical mixing, and atmospheric chemistry explain surface Arctic halogen observations Snow emissions of halogens impact atmospheric chemistry within a shallow layer near the surface Surface HOx concentrations are increased by up to a factor of 30 due to halogen chemistry